2013
DOI: 10.2478/jomb-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs Affect Protein, Lipid and DNA Oxidative Damage and Antioxidant Defense in Patients with Epilepsy

Abstract: List of abbreviations: AEDs -antiepileptic drugs, 8 -epi-PGF 2a -urinary isoprostanes, GPX -glutathione peroxidase, ILAE -International League Against Epilepsy, 8-OHdG -8-hydroxy-2'-deoxyguanosine, P-SH -protein thiol groups, RCD -reactive carbonyl derivatives, ROS -reactive oxygen species, SOD -superoxide dismutase. SummaryBackground: To get more insight into the effects of the most widely used antiepileptic drugs (AEDs) on the pro oxi dant/ antioxidant balance in epi lep sy, a comparative analysis of the byp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(60 reference statements)
2
8
0
Order By: Relevance
“…Peroxidative injury to plasma phospholipids may lead to severe cell damage (Ercegovac et al 2013). Surprising results with respect to lipid peroxidation were obtained in our study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Peroxidative injury to plasma phospholipids may lead to severe cell damage (Ercegovac et al 2013). Surprising results with respect to lipid peroxidation were obtained in our study.…”
Section: Discussionsupporting
confidence: 68%
“…To the best of our knowledge, no other positive effect of CBZ on lipids has been reported in fish to date. On the other hand, a positive effect of long-term treatment with CBZ on the antioxidant balance was described in humans (Ercegovac et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase in our patients was significantly higher than those in the control group. This is in agreement with several studies [11,35,36,37] . We suggest that GPX upregulation, in patients with epilepsy receiving AEDS, might be a consequence of induced GPX synthesis in the liver as a compensatory mechanism for decreased glutathione levels in the same group of patients.…”
supporting
confidence: 83%
“…Previous studies have measured the concentrations of eicosanoids (PGE 2 , TXA 2 , and PGI 2 ) in epileptic patients, in comparison with control group samples [28]. Thus, Ercegovac and colleagues showed that urinary 8-iso-PGF 2α (15-F 2t -IsoP) excretion was significantly increased (more than twofold) in patients with epilepsy compared to the control group [29]. These previous results indicate that epileptic patients could be subjected to augmented OS, compared to healthy individuals, at the systemic level.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the urinary excretion of the metabolite Ent-7-epi-7-F 2t -Dihomo-IsoP was greater in the epileptic group than in the control group (900472111 and 691671370 ng 24 h À 1 , respectively). Regarding AA oxidation markers (IsoPs), recent papers have reported urinary and blood levels of IsoPs in epileptic patients based on enzyme immunoassays (EIA) [29,35,36]. In patients with epilepsy, urinary 8-iso-PGF 2α (15-F 2t -IsoP) was significantly increased (1.81 ng/mg creatinine) compared to the control group (0.60 ng/mg creatinine) [29].…”
Section: Discussionmentioning
confidence: 98%